The effects of heating and cooling the spinal cord and hypothalamus on thermoregulatory behaviour in the pig - Carlisle, H. J. (1973)
1. The effects of warming and cooling the spinal cord and hypothalamus on operant thermoregulatory behaviour and posture have been studied in the pig at neutral and cold ambient temperatures. 2. Cooling the spinal cord increased and warming decreased the rate of obtaining thermal reinforcement. The response to cooling began with the onset of the stimulus and persisted for up to 5 min followed by a diminution in rate during the remaining 15 min of cooling. The peak of this `on' response was greater the lower the ambient temperature. The response to heating was a small reduction in rate of reinforcement. 3. The `on' response to cooling the spinal cord was related to changes in temperature of only the cervical region of the cord. 4. Cooling the hypothalamus led to an increase in the rate of obtaining heat and this increase was sustained during the 20 min of central cooling. Termination of cooling was followed by a marked depression in rate. Heating the hypothalamus had only a weak inhibitory effect on rate of reinforcement. 5. While working for external heat during periods when thermodes over the spine and in the hypothalamus were not being cooled, pigs lay in `cold defensive' prone positions 25% of the time and lay on their sides 75% of the time. During cooling of the spinal cord the time spent in the prone position was 95% at 5 and 15° C ambients and 71% at a 25° C ambient. During cooling of the hypothalamus the prone posture was adopted 50% of the time. 6. When the temperatures of the spinal cord and of the hypothalamus were changed in opposite directions, the operant response was determined by the temperature of the hypothalamus while the postural response was most frequently determined by the temperature of the spinal cord.